CHERISHING CUSTOMARY LAW: THE DISPARITY BETWEEN LEGISLATIVE AND JUDICIAL INTERPRETATION OF CUSTOMARY MARRIAGES IN SOUTH AFRICA - Charles Maimela; Ntebo Lauretta Morudu (Obiter, 2024)
The constitutional recognition of customary law in South Africa has opened a new conduit for the development of customary law. With the courts taking the lead in addressing customary law disputes, the interpretation of customary law has come with setbacks. This article argues that the development and reform strides made by the judicial and legislative institutions appear of modest benefit to the people they strive to protect, advance and regulate, especially during interpretation and reform. The article seeks to confront the judicial interpretation of customary law based on the recent High Court case of Sengadi v Tsambo. The court had to consider an application for four types of relief. The court deviated from the factual nature of customary law in relation to a spouse’s burial rights when it concluded that a valid customary marriage and all the validity requirements outlined under the Recognition of Customary Marriages Act had been met. Indicating the factuality of customary law when it relates to marriage and its link to burial rights, “that a male descendant of the household belongs to his paternal family, his place and existence being one with his paternal roots. His right to belong to his paternal family is absolute and customary.” The above ignored, yet crucial cultural practice informs the interpretation of customary law under the constitutional guise. The Constitution affirms the right to practise and observe one’s culture. In Sengadi v Tsambo, to determine the burial rights of a spouse, the court employed a narrow and strict interpretation instead of interpreting the cultural practice of bridal integration against a holistic customary background. The article advocates for courts to adopt purposive interpretational approaches in reforming customary law. It emphasises for the consideration of the interpretational rules and theoretical frameworks proposed by legal scholars to reflect the factual nature of customary law. As the positivist approach to customary law undermines the pluralistic nature of the South African legal system. The article pioneers for the recognition of living customary law as holistic, and an integral normative system of indigenous people of South Africa, while taking into account the history and context of this legal system.